Muscle weakness has a limited effect on motor control of gait in Duchenne muscular dystrophy. - Ines Vandekerckhove; Nathalie De Beukelaer; Marleen Van den Hauwe; Benjamin R Shuman; Katherine M Steele; Anja Van Campenhout; Nathalie Goemans; Kaat Desloovere; Marije Goudriaan (PLoS ONE, 2020)
Aim Our aim was to determine if synergy weights and activations are altered in Duchenne muscular dystrophy (DMD) and if these alterations could be linked to muscle weakness. Methods In 22 children with DMD and 22 typical developing (TD) children of a similar age, surface electromyography (sEMG) of the gluteus medius, rectus femoris (REF), medial hamstrings, tibialis anterior, and medial gastrocnemius (GAS) were recorded during gait. Muscle weakness was assessed with maximal voluntary isometric contractions (MVIC). Synergies were calculated with non-negative matrix factorization. The number of synergies explaining ≥90% of the variance in the sEMG signals (N90), were extracted and grouped with k-means cluster analysis. We verified differences in weights with a Mann-Whitney U test. Statistical non-parametric mapping (Hotelling's T2 test and two-tailed t-test) was used to assess group differences in synergy activations. We used Spearman's rank correlation coefficients and canonical correlation analysis to assess if weakness was related to modifications in weights and activations, respectively. Results For both groups, average N90 was three. In synergy one, characterized by activity at the beginning of stance, the DMDs showed an increased REF weight (p = 0.001) and decreased GAS weight (p = 0.007). Synergy activations were similar, with only a small difference detected in mid-swing in the combined activations (p<0.001). Weakness was not associated with these differences. Conclusion Despite the apparent weakness in DMD, synergy weights and activations were similar between the two groups. Our findings are in line with previous research suggesting non-neural alterations have limited influence on muscle synergies.